Effects of Climate Change and Artificial Intelligence on Mental Health and Academic Performance in Kenya - Omwenga, Michael Keari (CV. Literasi Indonesia, 2025)
Mental health conditions such as Stress, anxiety, trauma, and existential issues are all made worse by the increased frequency of catastrophic weather events and environmental degradation brought on by climate change. Potential solutions to lessen the negative effects of climate change on mental health are provided by digital advancements, especially artificial intelligence (AI) and digital phenotyping. Access and solution adoption concerns must be carefully considered when integrating digital tools into climate-related mental health care. The objective of the study was to address the effects of climate change on mental health and the scalability of digital interventions through cooperation amongst students. The study adopted a cross-sectional study design targeting college students in the Kisii region, Kenya. The convenience sampling method was used to sample 359 participants who were distributed questionnaires. Variables were examined using partial least squares-structural equation modelling (PLS-SEM), and data analysis was conducted using the specialized statistical programme SmartPLS in conjunction with multiple linear regression and confirmatory factor analysis (CFA). The results demonstrate that students' educational achievement and mental wellness are impacted by both the environment and artificial intelligence (AI). Additionally, the positive effects of AI and climate change on academic performance and mental health are amplified by digital learning, which serves as a positive moderating factor. These findings contribute to the discussion about using technology to improve education by showing how implementing AI and addressing climate change might benefit student performance and well-being.